Koszty w podejmowaniu decyzji w warunkach niepewności - Kaczyńska, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The subject of this paper are costs and their place in the decision-making process. Risk and uncertainty are typical for the economy. Cost analysis can reduce risk of economic activity. We have many useful tools: ratio analysis, financial reports, planning system, break-event point analysis. The paper presents some formal and mathematical methods, how to describe costs in the decision-making process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 113-121